2021
DOI: 10.1186/s12889-021-11613-y
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to reengage patients lost to follow up in HIV care in high income countries, a scoping review

Abstract: Background Despite remarkable achievements in antiretroviral therapy (ART), losses to follow-up (LTFU) might prevent the long-term success of HIV treatment and might delay the achievement of the 90–90-90 objectives. This scoping review is aimed at the description and analysis of the strategies used in high-income countries to reengage LTFU in HIV care, their implementation and impact. Methods A scoping review was done following Arksey & O′Malle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
(180 reference statements)
3
16
0
1
Order By: Relevance
“…That way, HIV/AIDS-positive MSM can have a good support system. Previous studies have shown that good relationships and support from both nurses and peers can improve the quality of life of HIV/AIDS-positive MSM and reduce loss to follow-up rates [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…That way, HIV/AIDS-positive MSM can have a good support system. Previous studies have shown that good relationships and support from both nurses and peers can improve the quality of life of HIV/AIDS-positive MSM and reduce loss to follow-up rates [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, referral-based models result in higher rates of PrEP-eligible individuals lost to follow-up than same-day start approaches 13,30 . Telephone calls to relay positive STI results also encourage engagement in HIV prevention discussions but do not allow for HIV testing without an in-person visit 31,32 …”
Section: Discussionmentioning
confidence: 99%
“…13,30 Telephone calls to relay positive STI results also encourage engagement in HIV prevention discussions but do not allow for HIV testing without an in-person visit. 31,32 The ED was the most frequent location for an STI diagnosis, but the competing priorities of ED staff often do not allow time for counseling and/or documentation. 7,33 Provider interventions are most successful when they are timely, and in this case, recommendations were not provided until after a patient had left the ED and results returned.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was interesting to detect that the longer the patient was initiated on ART, the lesser the risk of becoming LTFU. Interventions that strengthened reduced LTFU among new patients, such as strengthening electronic databases which show status at all health facilities, integrating services, community-based interventions, and making follow-ups with patients who meet the LTFU criteria, should be prioritized [ 24 ].…”
Section: Discussionmentioning
confidence: 99%